Pemanfataan Teknologi Informasi dan Komunikasi (TIK) dalam Pembelajaran Matematika - In In Supianti (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN MATHEMATICS LEARNING. The aims of this study are (1) to explain the definition of Information and Communication Technology (ICT); (2) to explain the importance of ICT used in Mathematics Learning; (3) to describe how much ICT used in Mathematics Learning in indoensia; (4) to elaborate the positive and negative effects of implementing ICT used in Mathematics learning. The methods used are literature review and description of interviews to educators and learners in the field of mathematics education. Information and Communication Technology is an electronic equipment consisting of hardware and software as well as any activities related to processing, manipulation, management, and transfer of information between media. It has has a function to produce quality and communicative information. In Indonesia, the use of Information and Communication Technology is still in integrating level, shown by the use of technology in learning. The utilization of information technology, in addition to efforts to overcome the technical problems of learning as a learning medium, as well as an effort to answer the substantial problem of learning as a source of teaching and encourage computer literacy acceleration in Indonesian society.